Rancang Bangun Alat Hypo-Hyperthermia Berbasis Arduino - ABA, Muhammad Ulin Nuha; Karim, Muhammad Nauval; Rofi i, Mohammad; Ningtias, Diah Rahayu (Universitas Semarang, 2020)
Hypo-hyperthermia tool is a devive that can stabilize body temperature which decreases or increases temperature dramatically. The design of hypo-hyperthermia devices has been made using Arduino Uno. Functional tests have also been carried out on the hypo-hyperthermia tool to determine the level of success and eligibility. This tool works by utilizing the flow of water to provide the temperature needed by the patient in order to obtain a normal temperature, namely by increasing the temperature of the blanket when the patient has hypothermia and lowering the temperature of the blanket when the patient has hyperthermia. The design of this hypo-hyperthermia tool uses Arduino uno as a processor and DS18B20 sensor for temperature readings. Heaters are also used as water heaters, condensers as water coolers, and water pumps to drive the water cycle from the appliance to the blanket and back to the appliance. The temperature and mode settings will be displayed on the LCD screen. Function test results obtained by comparing the value of the temperature reading in skin mode with a digital thermometer that is obtained an error value of 0.3%. This temperature difference is affected by the room temperature and body temperature of the patient which can change at any time. It was also obtained by comparison of the temperature reading values in blanket mode with a digital thermometer that is obtained the largest error value of 6% at a setting value of 25 °C and the smallest error value of 0.3% at a setting value of 30 °C. This temperature difference is influenced by the temperature of the room at the time of measurement on the blanket is also influenced by the thickness of the hose installed on the blanket, so that the cold temperature in the water is not absorbed properly.